1996
DOI: 10.1677/joe.0.1500121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of insulin-like growth factor-binding protein-2 on plasma clearance and transfer of insulin-like growth factors-I and -II from plasma into mammary-derived lymph and milk of goats

Abstract: Plasma clearance of insulin-like growth factors-I and -II (IGF-I and -II) and insulin-like growth factor-binding protein-2 (IGFBP-2) from lactating goats (n = 4) was determined following a single intravenous injection of the corresponding 125I-labelled human protein. Transfer of these proteins out of the vascular space was monitored by their subsequent appearance in mammary-derived lymph and milk. Clearance of 125I-IGFBP-2 from circulation was 0.37 +/- 0.06 ml/min/kg, which is markedly greater than that of 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…IGF-I, IGF-II and IGFBP-2 have been found in goat milk (Prosser 1996). Studies in goats have demonstrated that these peptides can cross from circulation to breast secretions (Prosser and Schwander 1996). Similarly, the most prevalent IGFBPs in pig milk include IGFBP-2, IGFBP-3, IGFBP-4 and an unidentified IGFBP with a molecular weight of 28 kDa (Monaco et al 2005).…”
Section: Types Of Igf-1mentioning
confidence: 99%
“…IGF-I, IGF-II and IGFBP-2 have been found in goat milk (Prosser 1996). Studies in goats have demonstrated that these peptides can cross from circulation to breast secretions (Prosser and Schwander 1996). Similarly, the most prevalent IGFBPs in pig milk include IGFBP-2, IGFBP-3, IGFBP-4 and an unidentified IGFBP with a molecular weight of 28 kDa (Monaco et al 2005).…”
Section: Types Of Igf-1mentioning
confidence: 99%